Analysis and Suppression of Pump Beam Alignment Error in SERF Co-Magnetometer - Qi Yuan; Wenfeng Fan; Haoying Pang; Xue Han; Zhuo Wang; Wei Quan (Photonics)
The beam angle error of the pump light in a K-Rb-21Ne spin-exchange relaxation-free atomic co-magnetometer (SERFCM) significantly degrades the efficiency of optical pumping and the system’s ability to suppress magnetic field noise. In this work, a system response model that incorporates the pump beam alignment error (PBAE) is established. The influence of PBAE on the scale factor, bandwidth, and magnetic noise response of the inertial output is analyzed. Theoretical results show that PBAE increases the internal magnetic field gradient, reduces the efficiency of nuclear spin hyperpolarization, and increases the nuclear spin relaxation rate, ultimately degrading the system’s scale factor, bandwidth, and magnetic noise suppression capability. Experimental results demonstrate that, compared to the original SERFCM with PBAE, aligning the pump laser using the proposed method improves the polarization strength of nuclear spins by approximately 10% and enhances magnetic noise suppression by 40%.